Przegląd potencjalnych podatków i opłat nakładanych na banki w obliczu globalnego kryzysu gospodarczego - Juszczyk, Sławomir; Snarski, Paweł (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
This paper aims the review the proposed taxes and fees that could be imposed on banks, presentation of the classifi cation of such taxes and fees too. Apart them the paper includes the description of the objectives and the presentation of arguments for and against their introduction. There are proposals for the harmonization of taxation of banks in the European Union